2020
DOI: 10.48550/arxiv.2005.11469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shapes and alignments of dark matter haloes and their brightest cluster galaxies in 39 strong lensing clusters

Taizo Okabe,
Masamune Oguri,
Sébastien Peirani
et al.

Abstract: We study shapes and alignments of 45 dark matter (DM) haloes and their brightest cluster galaxies (BCGs) using a sample of 39 massive clusters from Hubble Frontier Field (HFF), Cluster Lensing And Supernova survey with Hubble (CLASH), and Reionization Lensing Cluster Survey (RELICS). We measure shapes of the DM haloes by strong gravitational lensing, whereas BCG shapes are derived from their light profiles in Hubble Space Telescope images. Our measurements from a large sample of massive clusters presented here… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
2
2
1
Order By: Relevance
“…We find for both the observed and simulated clusters all probes are aligned with the dark matter with a mis-alignment angle of ∼ 20 degrees (depending on the cluster-centric radius). This is again consistent with Okabe et al (2020) who found a mean mis-alignment angle of θ = 22.2 ± 3.9 degrees. However, we do find that although the simulations are consistent with the observations, they do suggest a higher variance and random mis-alignments.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We find for both the observed and simulated clusters all probes are aligned with the dark matter with a mis-alignment angle of ∼ 20 degrees (depending on the cluster-centric radius). This is again consistent with Okabe et al (2020) who found a mean mis-alignment angle of θ = 22.2 ± 3.9 degrees. However, we do find that although the simulations are consistent with the observations, they do suggest a higher variance and random mis-alignments.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly we find the X-ray and weak lensing estimates are both more spherical than the strong lensing, whilst the cluster members BCG and the moment of inertia are much more elliptical. This is slightly inconsistent with Okabe et al (2020) who found that the probes all tended to be less elliptical than the strong lensing estimate.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Also, the observed tendency between the low-and high-redshift cluster samples is obtained regardless which weight is considered in order to compute the cluster orientation angle. Furthermore, the average projected ellipticity estimated for the high-redshift sample ( z = 0.35), is in agreement with the analysis of Okabe et al (2020) (see Fig. 9 of their paper) based on the cosmological hydrodynamical simulation Horizon-AGN (Dubois et al 2014).…”
Section: Halo Projected Ellipticitysupporting
confidence: 88%
“…This effect can be well modelled to obtain the projected ellipticity for individual targets as long as massive galaxy clusters or deep data are considered (e.g. Oguri et al 2010;Harvey et al 2019;Okabe et al 2020). Nevertheless, when lower mass halos are analysed, constraining the lensing signal is a hard task.…”
Section: Introductionmentioning
confidence: 99%